Adaptacja jako przekład intersemiotyczny - Hendrykowski, Marek (Przestrzenie Teorii, 2013)
Film adaptation is carried out by means of montage. This process is based on adjusting the obtained material and piecing together fragments which will be used once again and which an adapter has taken from the original work. It is montage, i.e. a selection and combination of moving pictures, which constitutes a new textual whole which is equivalent to the prototype, that forms a semiotic basis for and the essence of the adaptation process. The term “translation” can only be used in reference to film adaptation when we do not deal with full identicalness, but rather with functional similarity which does not allow one to fully equate a linguistic translation with screen adaptation.